2011
DOI: 10.1186/ar3337
|View full text |Cite
|
Sign up to set email alerts
|

Safety and clinical outcomes of rituximab therapy in patients with different autoimmune diseases: experience from a national registry (GRAID)

Abstract: IntroductionEvidence from a number of open-label, uncontrolled studies has suggested that rituximab may benefit patients with autoimmune diseases who are refractory to standard-of-care. The objective of this study was to evaluate the safety and clinical outcomes of rituximab in several standard-of-care-refractory autoimmune diseases (within rheumatology, nephrology, dermatology and neurology) other than rheumatoid arthritis or non-Hodgkin's lymphoma in a real-life clinical setting.MethodsPatients who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(110 citation statements)
references
References 61 publications
4
85
1
14
Order By: Relevance
“…Seventy-six of these articles had to be further excluded, as these provided incomplete data or had irrelevant objectives and were unsuitable for meta-analysis. Remaining 31 articles were included for meta-analysis (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Flowchart of the studies evaluated is represented in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Seventy-six of these articles had to be further excluded, as these provided incomplete data or had irrelevant objectives and were unsuitable for meta-analysis. Remaining 31 articles were included for meta-analysis (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Flowchart of the studies evaluated is represented in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Furthermore, the FDA approved the use of rituximab under certain circumstances for the treatment of chronic lymphocytic leukemia (CLL), non-Hodgkin lymphoma (NHL), rheumatoid arthritis, and granulomatosis with polyangiitis and microscopic polyangiitis (18). Although it is not approved for use in MS, it is quite often used off-label (19). …”
Section: Discussionmentioning
confidence: 99%
“…133 B cell depletion by a chimeric anti-CD20 antibody (rituximab) has substantial clinical benefit in many autoimmune and chronic inflammatory diseases, including type I diabetes, 134 RA, and SLE. 135 Rituximab-mediated B cell depletion was recently shown to improve endothelial function for at least 12 weeks in RA patients, at the same time as improved RA clinical disease activity and most inflammatory markers. 136 Consistent with these findings, a smaller trial reported favorable effects of anti-CD20 therapy on endothelial function.…”
Section: Targeting Effector T Cell Responsesmentioning
confidence: 99%